2017
DOI: 10.1111/jam.13379
|View full text |Cite
|
Sign up to set email alerts
|

An indoleacetic acid-producingOchrobactrumsp. MGJ11 counteracts cadmium effect on soybean by promoting plant growth

Abstract: In this study, we isolated a plant growth-promoting Ochrobactrum with the activity of mitigating Cd toxicity to plant roots. The Ochrobactrum can be considered as a potential bioaugmentation agent that promotes plant growth, especially in some agricultural systems, or that helps in the phytoremediation of Cd-contaminated soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The production of IAA by strain YH1 is higher (>100 μg ml −1 ) than most rhizobial stains previously reported and can be considered as an IAA-overproducer (Chiboub et al, 2016; Yu et al, 2017). It is observed that negative impact of metal accumulation inside plant tissues could be mitigated by the application of IAA (Nadeem et al, 2015).…”
Section: Discussionmentioning
confidence: 73%
“…The production of IAA by strain YH1 is higher (>100 μg ml −1 ) than most rhizobial stains previously reported and can be considered as an IAA-overproducer (Chiboub et al, 2016; Yu et al, 2017). It is observed that negative impact of metal accumulation inside plant tissues could be mitigated by the application of IAA (Nadeem et al, 2015).…”
Section: Discussionmentioning
confidence: 73%
“…Previous research demonstrated that reduction in root diameter may enable relatively higher growth rates and rapid resource acquisition through expansion of the root system coupled with lower investment in dry biomass [15]. These results suggest that induction of greater root length may be related to the production of IAA and/or other yet unknown metabolites produced by PGPB [16]. The benefits of inoculation on root length and plant growth may possibly involve the proximity of the site of interaction between PGPB and plant tissues [17].…”
Section: Discussionmentioning
confidence: 94%
“…; Yu et al . ). In this study, the SOD activity of the inoculated soybeans was significantly higher ( P < 0·05, n = 3) than that of the control plants in Cd‐contaminated soil, suggesting that the Cd 2+ ‐removing R. pusense KG2 improved soybean plant tolerance against Cd.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is unknown whether these Cd 2+immobilized micro-organisms can decrease the soil Cd availability for plants or not. Previous studies showed that some PGPR, such as IAA-producing bacteria, have been used to lower the Cd uptake of plants in Cd-contaminated soil (Yu et al 2017). A Cd-tolerant PGPR rhizobium increased the Cd concentration in the root of Lolium multiflorum Lam by enhancing the Cd availability and plant biomass but decreased the Cd concentration in the root and shoot of G. max (L.) (Guo and Chi 2014), suggesting that the same PGPR has a diverse effect on the different plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation